Eksistensi Tradisi Bersih Desa Baleturi Prambon Ngranjuk - Ramadhani, Adelia Fikriyah; Muzaiyana, Muzaiyana (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2022)
The Bersih Desa tradition is a traditional activity that is carried out once a year with the aim of praying for the safety of the village and being grateful for the blessings that have been given by God. The research entitled